2009
DOI: 10.1128/iai.00845-08
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium -Encoded MG309 Activates NF-κB via Toll-Like Receptors 2 and 6 To Elicit Proinflammatory Cytokine Secretion from Human Genital Epithelial Cells

Abstract: Mycoplasma genitalium has been implicated in several important reproductive tract syndromes in women, including pelvic inflammatory disease, cervicitis, and tubal factor infertility. The mechanisms of immune activation are unclear, and we sought to determine whether M. genitalium was capable of activating innate immune responses through ligation of highly expressed Toll-like receptors (TLR) of the genital tract. Using HEK293 cells expressing specific human TLR, viable M. genitalium and the recombinant C-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 46 publications
(50 reference statements)
4
70
1
Order By: Relevance
“…C. trachomatis LPS is associated with cytokine induction through TLR4/CD14-and NF-B-dependent signaling (15). In contrast to those reports, the present study showed that the IL-8 gene and NF-B were activated in HEK293 cells by E. chaffeensis Wakulla without transfection of any TLR genes, despite other reports that HEK293 cells require transfection with one or two specific TLR genes, such as the TLR2/6, TLR4, and TLR8 genes, to activate NF-B or cytokine genes (21,30,36). Taken together, our results indicate that E. chaffeensis does not require any TLRs to activate ERK and NF-B.…”
Section: Discussioncontrasting
confidence: 54%
“…C. trachomatis LPS is associated with cytokine induction through TLR4/CD14-and NF-B-dependent signaling (15). In contrast to those reports, the present study showed that the IL-8 gene and NF-B were activated in HEK293 cells by E. chaffeensis Wakulla without transfection of any TLR genes, despite other reports that HEK293 cells require transfection with one or two specific TLR genes, such as the TLR2/6, TLR4, and TLR8 genes, to activate NF-B or cytokine genes (21,30,36). Taken together, our results indicate that E. chaffeensis does not require any TLRs to activate ERK and NF-B.…”
Section: Discussioncontrasting
confidence: 54%
“…The polyubiquitination of IKK-␤ marks NF-B for rapid proteasomal degradation, leaving NF-B free to translocate into the nucleus and initiate gene expression (32,65). Activation of NF-B has been reported for other Mycoplasma species, including M. genitalium, M. fermentans, and M. pneumoniae (66)(67)(68). In those reports, lipoproteins from these mycoplasmas activated NF-B following stimulation of TLR-2 and TLR-6 in in vitro cell models.…”
Section: Discussionmentioning
confidence: 96%
“…This has been shown best by the experimental inoculation of the genital tracts of both male and female subhuman primates (204,213,223). Furthermore, cultured human vaginal and cervical epithelial cells in vitro have been found to be susceptible to M. genitalium, resulting in rapid cellular invasion; as a consequence of the immunogenic protein MG-309 activating NF-kappaB via Toll-like receptors, proinflammatory cytokines (interleukin-6 [IL-6], IL-8, and others) were secreted (141,142). This provides an insight into how acute inflammatory responses might be activated with their damaging sequelae.…”
Section: Immunological Responsesmentioning
confidence: 99%